Balancing Orthodoxy and Flexibility: Substantive and Accommodative Approaches to Women’s Rights in Qaradawi's Fiqh - Wibowo, Waskito; Hasbi, Rusli; Madi, Ahmed Abd Raziq Ali (Universitas Islam Negeri Jakarta, 2024)
The initiation of the minority fiqh concept for Muslims in countries with a non-Muslim majority is like a coin with two sides. On one side, it is seen as a threat to the established schools with their structured and well-defined methodologies, as it is often suspected of involving talfīq—combining opinions from various schools by selecting the most lenient fatwas. On the other hand, this concept represents an intellectual innovation aimed at helping minority Muslims remain committed to the principles of sharia amid a reality that does not fully support their religious practices. This paper critically investigates whether Qaraḍāwī adheres to a consistent methodology he designed, specifically whether he remains faithful to the principles he espouses or deviates by selectively borrowing opinions across schools. Taking some of his fatwas contained in his book entitled Fī Fiqh al-Aqalliyyāt al-Muslimah as the main object, this study argues that Qaraḍāwī, although, does talfīq in his fatwa by borrowing opinions from several ulama or schools, he consistently adheres to the methodology he established. This approach offers a legal framework that is accommodative yet rich in pragmatic nuances, resulting from a consistent synthesis of various opinions. Furthermore, on a broader scale, this concept provides a framework that balances flexibility with orthodoxy.AbstrakInisiasi gagasan fikih minoritas bagi umat Muslim di negara-negara dengan mayoritas non-Muslim ibarat koin dengan dua sisi. Di satu sisi, konsep ini dianggap sebagai ancaman bagi mazhab-mazhab yang memiliki struktur dan metodologi yang sudah mapan, karena kerap kali dicurigai mengandung unsur talfīq —menggabungkan pendapat dari berbagai mazhab dengan memilih fatwa yang paling ringan. Namun, di sisi lain, gagasan ini merupakan inovasi intelektual yang berupaya menjembatani Muslim minoritas agar tetap dapat berkomitmen pada prinsip-prinsip syariah di tengah realitas yang tidak sepenuhnya mendukung praktik keagamaan mereka. Tulisan ini bertujuan untuk mengkaji secara kritis apakah Qaraḍāwī konsisten dalam menerapkan metodologi yang ia rumuskan sendiri, khususnya apakah ia tetap berpegang pada prinsip-prinsip fikih minoritasnya atau justru hanya mengambil dan meminjam pendapat dari berbagai mazhab. Dengan mengambil beberapa fatwa yang terdapat dalam bukunya, Fī Fiqh al-Aqalliyyāt al-Muslimah, sebagai objek utama, artikel ini menunjukkan bahwa meskipun Qaraḍāwī melakukan talfīq dengan meminjam pendapat dari berbagai ulama atau madzhab, dia tetap berpegang pada metodologi yang ia bangun. Pendekatan ini menawarkan panduan hukum yang akomodatif namun juga penuh dengan nuansa pragmatis sebagai hasil dari sintesis berbagai pendapat yang dilakukan secara konsisten. Selain itu, dalam lingkup yang lebih luas, konsep ini menawarkan sebuah kerangka yang dapat menyeimbangkan antara fleksibilitas dengan ortodoksi.